A sensor placement algorithm for redundant covering based on Riesz energy minimization - Chai Wah Wu; Verma, Dinesh (2008 IEEE International Symposium on Circuits and Systems, 2008)
We present an algorithm for sensor placement with redundancy where each point in a 2-dimensional space is covered by at least k sensors under the constraint that all the sensors are located away from each other. We reduce the problem to distributing points evenly on the surface of a torus manifold and solve it computationally by minimizing the Riesz energy. We also study the case where the coverings are incrementally constructed. We illustrate our approach with numerical results and compare it to similar approaches in dispersed dither mask halftoning.